Relations between lifestyle and life satisfaction - Sánchez López, María del Pilar (1998)
The analysis of use of time during the week and the weekend provides an appropiate measure of the lifestyle. We describe the characteristics of the different groups and they are studied in relation to the lifestyle and work and family satisfaction. The concept of Congruence/Incongruence is used for analyzing the relationship between work and family environments. The conclusion is that those worlds are not independent. Moreover, lifestyle and satisfaction show some associations with demographic variables such as sex, kind of couple, and vital cycle (the age and the fact of having children).